ANALISIS PENERAPAN AKUNTANSI KEUANGAN PADA MASJID PARIPURNA DI PEKANBARU - Zulhelmy Mohd. Hatta (JURNAL AL-IQTISHAD, 2021)
This article is aims to facilitate and broaden insight into the application  of Plenary Mosque accounting based on PSAK 45 or ISAK 35, the research method is a survey (population is the entire Plenary Mosque of Marpoyan Damai District of Pekanbaru), as many as seven Plenary Mosque included in the SK Mayor of Pekanbaru. This research is based on field studies to obtain financial information as well as the management’s response to interviews conducted by the researcher. The result of this research is that the Plenary Mosque management has not made a general journal, general ledger, balance sheet or activity report and others as the mosque accounting is arranged.So that the application of accounting for the Plenary Mosque is getting better, the Goverment as a facilitator can conduct socialization and training to each of its management (providing assistance. Although the application of accounting has not been able to applied to the fullest, the management can begin to improve financial information by implementing activity reports in accordance with the Mosque’s accounting format.